Modeling higher order thinking skills and metacognitive awareness in English reading comprehension among university learners - Aziz, Musharraf; Rawian, Rafizah (Frontiers in Education, 2022)
Primarily, this study aimed to model the levels of Pakistani university learners’ higher order thinking skills (HOTS) in English reading comprehension to relate how explicit HOTS assessment can reveal learners’ strengths and weaknesses in reading as compared to traditional assessment of reading. Secondly, the study analyzed the effect of learners’ reading metacognitive awareness on the relationship between their HOTS levels and reading performance. It used a mixed-method approach. In the quantitative phase, an explicit HOTS-based reading test was designed using Bloom’s taxonomy to model learners’ HOTS levels in reading. Using stratified sampling, it was administered to the learners of bachelor of science in English (n= 200). Stratified sampling was performed for investigating the gender gap in HOTS levels. The learners’ reading metacognitive awareness was computed using Survey of Reading Strategies (Mokhtari & Sheorey, 2002). Descriptive analysis, independent sample t-test, correlation analysis and moderator analysis were conducted. It was found that the learners’ HOTS levels correlated with their reading performance while creating skill was the strongest, and evaluating skill was the weakest. Reading metacognitive awareness positively moderated the relationship between the learners’ HOTS levels and reading performance. In the qualitative phase, purposive stratified sampling was applied. A subsample (n= 6) was extracted from the core sample based on the high, average and low reading performance, and 3 groups were formed. A semi-structured interview was conducted to know learners’ opinions about using HOTS-based explicit assessment in reading, and their cognitive and metacognitive abilities. The thematic analysis of the qualitative data revealed that three out of six learners did not approve of the way they were assessed by the university. They informed that they had issues of cognitive and metacognitive control on English texts. The findings revealed that the majority of learners suffered low HOTS levels in English reading. The study provides implications for ESL teachers, assessors and policymakers to improve the learner performance to the possible optimal level, especially in underdeveloped contexts using traditional reading assessment.